Observations of Simultaneous Sperm Release and Larval Planulation Suggest Reproductive Assurance in the Coral Pocillopora acuta - Smith, Hillary A.; Moya, Aurelie; Cantin, Neal E.; van Oppen, Madeleine J. H.; Torda, Gergely (Frontiers in Marine Science, 2019)
Despite being an extensively studied group of corals, the reproductive biology of the scleractinian genus Pocillopora remains a mystery. Pocillopora acuta has been proposed to exhibit a mixed reproductive mode, sexually producing gametes (sperm and eggs) and asexually brooding larvae simultaneously within a single colony. Here, we report observations of night-time spawning of sperm during the peak monthly larval release period. We offer a new hypothesis for the regulation of sexual and asexual reproduction in the species and posit that sexual reproduction may occur more often than previously suggested. However, the success of internal oocyte fertilization and subsequent zygote development is dependent on sperm making contact with a fertile colony. We hypothesize that asexual development of larvae occurs when sperm is absent, but more extensive genetic, genomic, and histological data are required to determine the pathway by which unfertilized oocytes may develop. We also propose that this mixed mode of reproduction is an adaptation to mating failure, common in sessile marine invertebrates. The reproductive assurance enjoyed by the species may therefore be the key to its ecological and evolutionary persistence.